A recent study on islamic religious education teachers’ competencies in the digital age: a systematic literature review - Arif, Muhamad; Aziz, Mohd Kasturi Nor Abd; Ma'arif, Muhammad Anas (Intelektual Pustaka Media Utama, 2025)
Diverse research findings pertaining to the proficiency of Islamic religious education teachers may serve as a starting point, if not a benchmark, for the development of such instructors' proficiency, particularly with regard to the proficiencies that are imperative for educators in the digital age. Consequently, this study aims to investigate the competencies of Islamic religious education teachers that have been mentioned most frequently in research over the past decade, as well as strategies for developing those competencies and technological (digital) competencies. To achieve this aim, this study employed a systematic literature review method by utilizing publication data spanning a decade (2013–2023) to investigate a particular theme. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) was utilized to evaluate the findings. This research shows findings regarding teachers' obligations to develop technological (digital) competencies, in addition to the four teacher competencies (pedagogical, professional, personal, and social). The aforementioned conditions are predicated on the necessity for collaborative, creative, and creative learning, which makes it highly sought after by students. In contrast, forthcoming investigations should strive to gather empirical data regarding approaches to cultivating digital proficiency among Islamic religious education instructors, given the prevailing inclination towards learner-centered learning in the twenty-first century as opposed to teacher-centered learning.